Functional Neurological Disorders as Seen by a Cohort of General Practitioners in Northern Italy: Evidence From an Online Survey - Marotta, Angela; Fiorio, Mirta; Fracasso, Isabella; Franchini, Carlo Andrea; Defazio, Giovanni; Tinazzi, Michele (Frontiers in Neurology, 2021)
General practitioners (GPs) provide primary care and advise their patients on which diagnostic and therapeutic pathways they judge most appropriate. For patients with functional neurological disorders (FND), receiving a proper explanation of diagnosis by their GP from the very beginning may drastically improve prognosis. Novel approaches to the diagnosis and treatment of FND have important implications for effective management. The aim of this study was to investigate Italian GP opinion and knowledge about FND in light of new approaches to the illness. To do this, we evaluated the responses to a 13-item web-based survey completed by 133 GPs practicing in northern Italy. Psychological terms to describe FND were more frequently used than functional neurological disorder and mental illness was considered an important predictor of diagnosis. Referral to a neurologist rather than to a psychiatrist was largely preferred, while physiotherapy consultation was seldom recognized as a valuable approach to treating FND. Overall, the survey findings suggest that knowledge about novel approaches to FND is somewhat lacking. Currently, GPs appear to be transitioning from a classical psychological view of the disorder toward a more modern conceptualization, in which neurobiological, psychological, and social factors all play an important role. Professional education during this transition would be an advantageous way to optimize physician management of FND and to enhance diagnosis, explanation, and management across primary and secondary care pathways.